The Accuracy of Information Recipients and Consent Givers for Informed Consent in Hospitals - Adhayati, Baety; Putrihamidah, Diyanthie Aulia; Louisa, Melva; Sodikin, Ali (Media Publikasi Cendekia Indonesia, 2024)
This study aimed to assess the accuracy of the party receiving information and giving consent in the hospital. This type of research is observational and was conducted at Public Hospital of Banten Province (RSUD Banten) and Dr. Drajat Prawiranegara Public Hospital in 2024. The minimum sample size used was 94 samples taken using consecutive sampling methods. This study used a checklist as a record to check the completeness of the informed consent form and approval sheet by the SOP and applicable legal basis. Data analysis is descriptive of the accuracy of the party receiving information and giving consent. The study observed 28 pieces of information and consent being received and given by the right party, while the wrong party signed 66 (70.2%) consents for medical procedures. The study's focus on the accuracy of the party receiving information and giving consent in the hospital is a contribution to a monitor process of informed consent in hospital according to principles of patient’s competency